An Economical Approach to Ethnic Asian Rhinoplasty - Zelken, Jonathan; Chang, Chun-Shin; Chuang, Shiow-Shuh; Yang, Jui-Yung; Hsiao, Yen-Chang (Facial Plastic Surgery, 2016)
Septal cartilage is deficient in Asians seeking augmentation rhinoplasty. Economized utilization of resources is necessary for durable tip enhancement that complements a dorsal implant. We introduce a modified tongue-in-groove method designed to transmit forces across the dorsum, eliminating the need for robust caudal support and prioritizing nasal lengthening and tip projection. We aim to promote the roundness index parameter and demonstrate the feasibility of a novel method in the context of Asian rhinoplasty. Between 2012 and 2014, a total of 104 Taiwanese patients underwent rhinoplasty with dorsal augmentation and lengthening with a modified tongue-in-groove technique. The concept borrows from methods established by Byrd, Guyuron, and Toriumi but distinguished by exaggerated forward positioning of a septal extension graft. Paired extended spreader grafts obviate the need for a columellar strut. Soft-tissue changes were analyzed with photogrammetry. A new parameter, the roundness index, was measured. Tip projection, dorsal length, nasal height, alar and columellar length increased significantly after 5.5 months of follow-up. Nasal tip angle, roundness, columella-labial angle, and nostril axis inclination decreased. There were no statistically significant differences in the magnitude of change in patients followed for less than and greater than 6 months. The most common complication was new or persistent tip deviation in five cases (5%). This technique was designed for a nasal anatomy typified by deficient septal cartilage. Significant photogrammetric changes were maintained after 6 months. Economized tissue allocation, dorsal septal load sharing, and relative independence from caudal support are key features of this feasible method.
Keywords: rhinoplasty; spreader graft; ethnic Asian rhinoplasty